Analisis uji validitas LKS berorientasi HOTS dalam model inkuiri terbimbing pada materi fluida statik di kelas XI fisika SMA/MA - Nurhijjah Tiur S; Silvi Yulia Sari; Yenni Darvina (PILLAR OF PHYSICS EDUCATION, 2019)
Learning physics cannot be carried out simply by memorizing, listening, and seeing without experiencing. Physics learning requires students to be able to think critically, creatively, have problem solving skills, and be able to make decisions. In order for students to get meaningful lessons in physics, they need to find their own concepts to be understood. This can be achieved by using an appropriate learning model. One learning model that can be used is guided inquiry. This study aimed to determine the validity of HOTS-oriented worksheets in the guided inquiry model of static fluid learning material. This type of research was Research and Development (R&D). The development steps carried out by Borg and Gall. The instrument used in the study was the validity test sheet. The data analysis technique used is descriptive statistical analysis.Based on the data analysis, the results show that the HOTS-oriented worksheet in the guided inquiry model on static fluid learning material has a high validity value of 86.65. It means, the learning materials are ready to use in learning process.